Distributed secondary control of microgrids with unknown disturbances and non-linear dynamics - Hu, Shunwei; He, Liping; Zhao, Haodong; Liu, Huawei; Liu, Xueqiang; Qiu, Jianlong (Frontiers in Energy Research, 2023)
In this paper, the voltage and frequency regulation of microgrid with unknown disturbance and nonlinear dynamics is studied. First, the distributed secondary control protocol is designed to reduce the communication burden between generators and solve the voltage and frequency deviation. Secondly, a consensus protocol for secondary control of voltage and frequency is designed based on the idea of multi-agent consensus, which can indirectly ensure that the voltage and frequency to be adjusted reach the reference value when the consensus is realized. In addition, considering the unknown disturbance in the microgrid, a sliding mode control (SMC) strategy based on disturbance observer is designed to overcome the influence of disturbance and reduce chattering, and the designed SMC scheme ensures the finite time accessibility of sliding mode surface. Based on the above design, sufficient conditions for realizing voltage and frequency regulation are given, and the effectiveness of the design scheme is verified through simulation.